Effects of Inertia on Evolutionary Prisoner＇s Dilemma Game - 杜文博 曹先彬 刘润然 王震 (理论物理通讯：英文版, 2012)
Considering the inertia of individuals in real inertia of players is introduced into evolutionary prisoner＇s life, we propose a modified Fermi updating rule, where the dilemma game （PDG） on square lattices. We mainly focus on how the inertia affects the cooperative behavior of the system. Interestingly, we find that the cooperation level has a nonmonotonic dependence on the inertia： with small inertia, cooperators will soon be invaded by defectors; with large inertia, players are unwilling to change their strategies and the cooperation level remains the same as the initial state; while a moderate inertia can induce the highest cooperation level. Moreover, effects of environmental noise and individual inertia are studied. Our work may be helpful in understanding the emergence and persistence of cooperation in nature and society.